Gene tracing analysis reveals the contribution of neural crest‐derived cells in pituitary development - Ueharu, Hiroki; Yoshida, Saishu; Kikkawa, Takako; Kanno, Naoko; Higuchi, Masashi; Kato, Takako; Osumi, Noriko; Kato, Yukio (Journal of anatomy, 2017)
The anterior pituitary originates from the adenohypophyseal placode. Both the preplacode region and neural crest (NC) derive from subdivision of the neural border region, and further individualization of the placode domain is established by a reciprocal interaction between placodal precursors and NC cells (NCCs). It has long been known that NCCs are present in the adenohypophysis as interstitial cells. A recent report demonstrated that NCCs also contribute to the formation of pericytes in the developing pituitary. Here, we attempt to further clarify the role of NCCs in pituitary development using P0‐Cre/EGFP reporter mice. Spatiotemporal analyses revealed that GFP‐positive NCCs invaded the adenohypophysis in a stepwise manner. The first wave was detected on mouse embryonic day 9.5 (E9.5), when the pituitary primordium begins to be formed by adenohypophyseal placode cells; the second wave occurred on E14.5, when vasculogenesis proceeds from Atwell's recess. Finally, fate tracing of NCCs demonstrated that NC‐derived cells in the adenohypophysis terminally differentiate into all hormone‐producing cell lineages as well as pericytes. Our data suggest that NCCs contribute to pituitary organogenesis and vasculogenesis in conjunction with placode‐derived pituitary stem/progenitor cells.